2011
DOI: 10.1111/j.1750-3841.2010.01945.x
|View full text |Cite
|
Sign up to set email alerts
|

Volatile Composition of Pomegranates from 9 Spanish Cultivars Using Headspace Solid Phase Microextraction

Abstract: Fruits of 9 Spanish pomegranate cultivars were analyzed for quality parameters, volatile composition, and sensory profile. Volatile compounds were extracted using headspace solid phase micro-extraction (HS-SPME) and analyzed by gas chromatography-mass spectrometry (GC-MS) and flame ionization detector (GC-FID). Twenty-one compounds were found in the headspace of fresh pomegranate juices, including aldehydes, monoterpenes, and alcohols. The most abundant compounds were hexanal, limonene, trans-2-hexenal, and ci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
89
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 106 publications
(99 citation statements)
references
References 13 publications
8
89
2
Order By: Relevance
“…In this order, Katirbasi would be the most astringent and Mollar de Elche the less. This in line with Melgarejo et al [44] who reported that Mollar de Elche family is characterized by its sweetness, low sourness, and soft and easy to eat pith.…”
Section: Hydrolyzable Tanninssupporting
confidence: 77%
See 4 more Smart Citations
“…In this order, Katirbasi would be the most astringent and Mollar de Elche the less. This in line with Melgarejo et al [44] who reported that Mollar de Elche family is characterized by its sweetness, low sourness, and soft and easy to eat pith.…”
Section: Hydrolyzable Tanninssupporting
confidence: 77%
“…The other cultivars had intermediate maturity indexes. In generally, our result for Mollar de Elche (49.18) was lower than Melgarejo et al [44,54] [62].…”
Section: Physical Characteristicscontrasting
confidence: 53%
See 3 more Smart Citations